STRATEGI PENGAMBILAN KEPUTUSAN STRATEGIS DALAM MENGHADAPI PANDEMI COVID-19 DI INDONESIA: SEBUAH LITERATUR REVIEW - Dina Subagia; Iko Aulya Prabandari Santoso; M Maryanti; Rizkia Mutiara Ramadhani (Jurnal Manajemen Bencana (JMB), 2020)
This paper discussed what strategic steps have been taken by the Indonesian government as policy makers during the emergency period of the COVID-19 pandemic in order to protect the entire nation and Indonesian bloodshed from all forms of threats in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia. This paper uses a literature approach. The findings of this study are that the government has prepared three strategies for handling COVID-19, namely handling health emergencies, social security networks, and economic resilience. By knowing the strategies and programs issued to carry out these strategies, it can be concluded that in terms of planning, regulation and governance, the government has carried out its functions properly, but what needs to be underlined is that it is not only appropriate but also fast.